Efektivitas UU No.11 tahun 2012 (SPPA)terhadap batas minimum usia pidana anak berdasarkan hukum positif di Indonesia - Yolanda Febriani; Asep Suherman (CV. ITTC INDONESIA, 2024)
Law No. 11 of 2012 on the Juvenile Criminal Justice System (SPPA) aims to protect the rights of children in conflict with the law, including establishing the minimum age of criminal responsibility in Indonesia. This article seeks to analyze the effectiveness of the implementation of Law No. 11 of 2012 in setting the minimum age for juvenile criminal liability. The research employs a normative juridical method with a statutory approach and case analysis. The findings reveal that the minimum age for criminal responsibility set by the law has not been fully effective in reducing juvenile crime rates, largely due to the lack of law enforcement and public awareness. It is recommended to improve the application of more educational alternative sanctions and strengthen the child protection system.